1991
DOI: 10.1021/om00048a025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of ruthenium amide-phosphine complexes. Facile conversion of a ruthenium amide to a ruthenium amine via dihydrogen activation and orthometalation. X-ray structure of RuCl(C6H4PPh2)[NH(SiMe2CH2PPh2)2]

Abstract: The reaction of LiN(SiMe2CH2PPh2)2 with RuCl2(PPh3)3 leads to the formation of the ruthenium amide complex RuCl(PPh3)[N(SiMe2CH2PPh2)2]. This complex reacts with H2 to form two isomeric amine-hydride derivatives of the formula RuCl(PPh3)H[NH(SiMe2CH2PPh2)2]. Reaction of RuCl(PPh3)[N-(SiMe2CH2PPh2)2] with MeLi, Me3SiCH2Li, or H2C=CHCH2MgCl does not lead to the expected hydrocarbyl derivative; rather, ortho metalation occurs to generate Ru(C6H4PPh2)[N(SiMe2CH2PPh2)2]. Attempts to displace the PPh3 ligand of RuCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 0 publications
5
71
0
Order By: Relevance
“…For the nitrosyl species, SBM is slightly more accessible, while OA/RE is preferred with the anionic CO analogue. 34 The major geometric differences between the SBM transition state and OA/RE intermediate are in the C-W-C angles (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) • wider in the OA intermediate) and W ◊ ◊ ◊ H distances (ca. 0.1 Å shorter in the OA intermediate).…”
Section: Sbm At L N M=cr 2 and L N M≡cr Bondsmentioning
confidence: 99%
“…For the nitrosyl species, SBM is slightly more accessible, while OA/RE is preferred with the anionic CO analogue. 34 The major geometric differences between the SBM transition state and OA/RE intermediate are in the C-W-C angles (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) • wider in the OA intermediate) and W ◊ ◊ ◊ H distances (ca. 0.1 Å shorter in the OA intermediate).…”
Section: Sbm At L N M=cr 2 and L N M≡cr Bondsmentioning
confidence: 99%
“…In related reactions, Fryzuk et al have reported dihydrogen activation across the chelating amido ligand of Ru(Cl)(PPh 3 )[N(SiMe 2 CH 2 PPh 2 ) 2 ], [108] and Morris et al have demonstrated that dihydrogen activation by a Ru II amido yields a complex in which the HÀH bond becomes protic-hydridic in character (i.e., H dÀ ···H d+ ). [109] Although H 2 activation by complex 1 is facile, complex 1 undergoes an intramolecular CÀH activaScheme 5.…”
Section: Càh Activation With Late Transition Metal Hydroxide and Relamentioning
confidence: 99%
“…5 Despite their importance, reports of well-defined reactions with late(r) transition metal systems are rare and mechanistic studies are limited. [5][6][7][8] Recently, C-H activation of hydrocarbons via net 1,2-addition of C-H bonds across metal-heteroatom bonds using late transition metals (with g6 d-electrons) bearing formally anionic ligands (e.g., -NHR or -OR) has been reported. [9][10][11][12][13][14] Despite interest in these C-H and H-H bond transformations, questions regarding the mechanism remain.…”
Section: 2mentioning
confidence: 99%
“…We initially presumed this straightforward pathway, which is consistent with the general notion of reactions with related systems. 5,7,8,13,19,20 Monitoring ( 1 H NMR) the reaction of 2 with H 2 and a plot of [2] versus time reveals an induction period ( Figure 2A). The observation of an induction period led us to consider Pt(s) as a heterogeneous catalyst.…”
Section: 2mentioning
confidence: 99%